THE ROLE OF HALAL AWARENESS IN AFFECTING COSMETIC PURCHASE BEHAVIOR - Hazmi, Faiqul; Utami, Cahyaning Budi (Fakultas Ekonomi dan Bisnis Islam - Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
Abstract: The critical point of halal beauty products leads many consumers to prioritize the halal status of the products they purchase. In Indonesia, a country with a predominantly Muslim population, the demand for halal beauty products has made it the world’s second-largest market in this sector. This study applied online questionnaire. The study retained a total of 114 valid responses. Findings from this study indicate that the halal label significantly influences both halal awareness and purchase intention. Additionally, halal awareness has a substantial effect on purchase intention, which in turn significantly impacts purchasing behavior. However, halal awareness does not moderate the relationship between the halal label and purchase intention. Future research could consider examining product characteristics as factors influencing purchase intentions and behavior. The practical implications of this study include: (1) beauty manufacturers are encouraged to certify their products as halal; and (2) fostering halal awareness should be a shared responsibility across stakeholders. Keywords: halal label, halal awareness; intention to buy; purchase behaviour. Abstract: Titik kritis ketidakhalalan produk kecantikan membuat beberapa konsumen memperhatikan status kehalalan produk yang akan dibelinya. Indonesia dengan penduduk mayoritas muslim juga menjadi negara terbesar ke dua dalam pembelian produk kecantikan halal. Penelitian ini menggunakan kuesioner online dalam pengumpulan datanya. Jumlah respon yang valid sebesar 114. Hasil penelitian ini menunjukkan bahwa label halal berpengaruh signifikan terhadap kesadaran halal dan intensi untuk membeli, kesadaran halal memiliki pengaruh signifikan terhadap intensi untuk membeli, intensi untuk membeli berpengaruh signifikan terhadap perilaku pembelian, kesadaran halal terbukti tidak mampu memoderasi hubungan label halal terhadap intensi untuk membeli. Implikasi praktis dari studi ini (1) produsen produk kosmetik agar mendaftarkan produknya untuk memperoleh sertifikasi halal; (2) peningkatan kesadaran halal menjadi tanggungjawab bersama. Keywords: label halal; kesadaran halal; intensi membeli, perilaku pembelian.